The Separation of Church and State in the Current Philippine Context - Sagut, Joel C. (Politikologija religije, 2022)
This paper is an attempt to show that the doctrine of the separation of Church and State is enshrined in the laws of the Republic of the Philippines and that Philippine jurisprudence has repeatedly referred to this doctrine in the resolution of cases that deal with the intersections of the Church and State. It moreover argues that the understanding of this doctrine in Philippine law and jurisprudence, though borrowed largely from the West, could not be interpreted to an extent where public expressions of religion and the involvement of churches in public life become prohibited. Instead, the application of this doctrine in the context of the Philippines is primarily aimed at safeguarding the welfare of religion. This, therefore, implies that religions and churches are never impeded in their actions even in public life as long as they do not pose clear and present harm to the people. This in turn becomes an invitation for religions and churches to become truthful to their mission of working for the wellbeing of the people, even if it also implies that to effectively carry out that mission, churches themselves, and especially the Catholic Church, must continuously exercise its reflective attention to what it is called to do and must do, especially in times when her service and voice are needed by the people.